Design Analysis of the Hydraulic System for Containerized Oil Boom - Zaman, Muhammad Badrus; Santoso, Agoes; Fahadh, Malik (International Journal of Marine Engineering Innovation and Research, 2025)
Oil Boom is an equipment used for efforts to overcome the oil spills that occur in the sea. The function of the Oil Boom itself is to limit the oil spill so that it doesn't spread too wide. The hydraulic system is a system that utilizes pressurized liquid fluid as the actuator drive media. The concept of the technical analysis of this system is the design of the winch system using a hydraulic motor which is a driving device as well as a roller of an oil boom that has a length of 2 kilometers and then stored into the drum that has been designed. All components are in a container package that has been designed to place the position and layout. To see the advantages and disadvantages of the system design, technical analysis is carried out. From the results of data processing it can be calculated for the torque moment of the drum which is equal to 9,344.416 Nm and weighs 242.697 kg. BLACKBRUIN BBC05 type hydraulic motor has been determined which has a torque of 10,360-13,305 Nm and a pressure of 350-400 bar. After the total air demand for oil boom as long as 2 km is known, which is equal to 552,951 cm3, the next step is to select the right compressor. Selected type TANABE TASK-25110 compressor with a capacity of 1,020 m3/hour. That way, it can be determined the air filling time for the oil boom is 0.542 hours = ±35-40 minutes.